Polymer brushes showing non-fouling in blood plasma challenge the currently accepted design of protein resistant surfaces - Rodriguez-Emmenegger, Cesar; Brynda, Eduard; Riedel, Tomas; Houska, Milan; Šubr, Vladimir; Alles, Aldo Bologna; Hasan, Erol; Gautrot, Julien E; Huck, Wilhelm T S (Macromolecular rapid communications, 2011)
Ultra-low-fouling poly[N-(2-hydroxypropyl) methacrylamide] (poly(HPMA)) brushes have been synthesized for the first time. Similar to the so far only ultra-low-fouling surface, poly(carboxybetaine acrylamide), the level of blood plasma fouling was below the detection limit of surface plasmon resonance (SPR, 0.03 ng·cm(-2)) despite being a hydrogen bond donor and displaying a moderate wettability, thus challenging the currently accepted views for the design of antifouling properties. The antifouling properties were preserved even after two years of storage. To demonstrate the potential of poly(HPMA) brushes for the preparation of bioactive ultra-low fouling surfaces a label-free SPR immunosensor for detection of G Streptococcus was prepared.
Keywords: kyseliny polymethakrylové; biosenzitivní techniky; povrchové vlastnosti; Adsorption; Blood Proteins; Polymethacrylic Acids; Humans; krevní proteiny; lidé; Surface Properties; adsorpce; Biosensing Techniques